2009
DOI: 10.1183/09031936.00101108
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle exhaust outside the home and onset of asthma among adults

Abstract: Few studies have investigated the relationship between vehicle exhaust and the new onset of asthma among adults. The aim of the present prospective cohort study was to investigate the relationship between the cumulative incidence of asthma and onset of asthma among adults and vehicle exhaust concentrations at home.Participants from three Swedish cities included in the Respiratory Health in Northern Europe cohort constituted the study population. Exposure at each participant's home was calculated using dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 27 publications
6
81
0
Order By: Relevance
“…Furthermore, estimation of ambient concentrations at home addresses does not fully capture participant exposure because it cannot account for infiltration into the home or potentially important exposures from commuting or other activities. Nonetheless, our exposure model represents a substantial improvement over the previous generation of nearest monitor (4) and may be more comparable to high-quality dispersion models (3,24) used in previous publications on incident asthma because our model better captures within-region and between-region contrasts in air pollution, reduces exposure misclassification through spatial smoothing, and has overall excellent model performance. We anticipate that misclassification in exposure, which would not be expected to differ by case status, would tend to attenuate the observed associations rather than lead to spurious positive ones.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, estimation of ambient concentrations at home addresses does not fully capture participant exposure because it cannot account for infiltration into the home or potentially important exposures from commuting or other activities. Nonetheless, our exposure model represents a substantial improvement over the previous generation of nearest monitor (4) and may be more comparable to high-quality dispersion models (3,24) used in previous publications on incident asthma because our model better captures within-region and between-region contrasts in air pollution, reduces exposure misclassification through spatial smoothing, and has overall excellent model performance. We anticipate that misclassification in exposure, which would not be expected to differ by case status, would tend to attenuate the observed associations rather than lead to spurious positive ones.…”
Section: Discussionmentioning
confidence: 91%
“…An analysis of the Danish Diet, Cancer and Health cohort of adults aged 50-65 years found an association between NO 2 and new hospitalization for asthma (977 cases) (19). A prospective cohort in Swedish cities found an elevated risk of incident asthma for NO 2 with 55 cases (24). An earlier case-control study in Sweden by the same authors of the Swedish cohort study found an elevated but nonsignificant association with NO 2 (203 cases) (25).…”
Section: Discussionmentioning
confidence: 93%
“…These chemicals are irritating and the authors interpret their results as not being caused by sensitising agents (MedinaRamon et al 2005). Also the relatively low level of ambient irritating air pollution from traffic exhausts in cities in Sweden (Modig et al 2009) and 14 other cities in the European Community (Jacquemin et al 2009) give an excessive risk for asthma.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Additionally, fuel adulterants such as naphtha, n-butanol, and kerosene, found in the adulterated trawler diesel, are known threats to human health. Past studies investigating the respiratory health of fishermen have found mixed results about health outcomes and have not focused on the identification of specific exposures.…”
Section: Introductionmentioning
confidence: 99%